Development of Pineapple Products in Wang Pong Sub-District, Pran Buri District, Prachuap Khiri Khan Province - Phueakbuakhao, Wipavanee; Klahan, Rungkan; Chaiwong, Krit; Maksiri, Wanida; Chupwa, Chuangchai (Journal of Human and Society, Sisaket Rajabhat University, 2022)
This research had objectives to: 1) to study the potential of community product from pineapple processing of Wang Pong sub-district, Pran Buri district, Prachuap Khiri Khan Province, and 2) to develop prototype products from pineapple processing to enhance the community economy of Wang Pong sub-district, Pran Buri district, Prachuap Khiri Khan province. The researchers used the mixed method research methodology. By using quantitative study, the data were collected from 388 people in pineapple processing groups in Wang Pong sub-district, Pran Buri district, Prachuap Khiri Khan province, by using the questionnaire. By using the qualitative study, the data were collected by using in-depth interview from 9 key informants, selected by using purposive sampling method, consisting of president, committee, and members of community enterprise in Wang Pong Subdistrict, and the agricultural extension officer in Wang Pong sub-district, Pran Buri district, Prachuap Khiri Khan province. The statistic used in this research are, frequency, percentage, mean, standard deviation, and descriptive writing. The research results found out that: 1) The potential of community product from pineapple of Wang Pong sub-district, Pran Buri district, Prachuap Khiri Khan province, revealed that the potential was overall at a moderate level. When all aspects were individually considered, they could be ranked in descending order of their means as follows: community enterprise member administration, leaders and community enterprise administration, community enterprise management planning, information and knowledge management, good or service management, and market administration, and 2) The development of prototype products from pineapple processing for enhancing community economy of Wang Pong sub-district, Pran Buri district, Prachuap Khiri Khan province, revealed that the community could develop pineapple products to create value addition and could develop a new product from pineapple wastes, which could create jobs, careers, and enhance the income to the community, by “developing Bromelain product from pineapple peels, crowns, and roots for tenderizing meat”.